Experimental investigation and thermodynamic description of the Fe–Ta–Ti system. (June 2019) - Yang, Bo; Guo, Cuiping; Li, Changrong; Du, Zhenmin
Abstract: The phase equilibria at 1473, 1373 and 1273 K in the Fe–Ta–Ti system were investigated by means of Scanning Electron Microscopy (SEM) with Energy Dispersive Spectrometer (EDS) and X-ray Diffraction (XRD). The experimental results indicated that Fe2 Ta and Fe2 Ti formed the continuous solid solution phase Fe2 (Ta, Ti). No ternary compound was found in this system. The temperature of invariant reaction liquid + Fe7 Ta6 → FeTi + bcc(Ta, Ti) was measured as 1431 K by Differential Thermal Analysis (DTA). Based on the experimental results in the present work, the Fe–Ta–Ti system was optimized using CALPHAD technique. A set of self-consistent thermodynamic parameters for the Fe–Ta–Ti system was obtained, and the experimental isothermal sections at 1473, 1373 and 1273 K were reproduced well. Highlights: The isothermal sections of the Fe–Ta–Ti system at 1473, 1373, and 1273 K were determined. The temperature of the invariant reaction liquid + Fe7 Ta6 → FeTi + bcc(Ta, Ti) was confirmed at 1431 K. A set of self-consistent thermodynamic parameters of the Fe–Ta–Ti system was obtained.